2021
DOI: 10.1200/jco.2021.39.3_suppl.360
|View full text |Cite
|
Sign up to set email alerts
|

A phase II/III randomized double-blind study of octreotide acetate LAR with axitinib versus octreotide acetate LAR with placebo in patients with advanced G1-G2 NETs of non-pancreatic origin (AXINET trial-GETNE-1107).

Abstract: 360 Background: Angiogenesis plays an important role in NET development and progression. Axitinib is a potent and selective VEGFR-1,2,3 inhibitor, with proven activity against several vascular-dependent solid tumors. The aim of this randomized, double-blind phase II/III study was to assess the efficacy of axitinib in patients with advanced G1-2 extra-pancreatic NETs. Methods: Eligible pts were randomized (1:1) to receive octreotide LAR (30 mg IM q4w) with axitinib (5 mg BID) or placebo BID until disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Significant heterogeneity was observed across the subset of studies on TKI (I 2 = 89.8%, p -value < 0.0001; Figure 2 ). A funnel plot was also produced demonstrating asymmetry ( Figure S1A ), that was mainly attributed to the recent studies on novel TKIs by Xu et al on surufatinib in pancreatic NENs and by Carbonero et al on axitinib in extra-pancreatic NENs (Galbraith’s plot; Figure S1B ) [ 29 , 30 ]. Egger’s test showed no indication of publication bias across the included studies ( p -value > 0.05).…”
Section: Resultsmentioning
confidence: 95%
“…Significant heterogeneity was observed across the subset of studies on TKI (I 2 = 89.8%, p -value < 0.0001; Figure 2 ). A funnel plot was also produced demonstrating asymmetry ( Figure S1A ), that was mainly attributed to the recent studies on novel TKIs by Xu et al on surufatinib in pancreatic NENs and by Carbonero et al on axitinib in extra-pancreatic NENs (Galbraith’s plot; Figure S1B ) [ 29 , 30 ]. Egger’s test showed no indication of publication bias across the included studies ( p -value > 0.05).…”
Section: Resultsmentioning
confidence: 95%
“… 19–21 These investigations led to the FDA approval of sunitinib in treating progressive, well-differentiated pancreatic NET for patients with locally advanced or metastatic disease. 22 Although no antiangiogenic drugs have been granted FDA approval for NET of pulmonary origin yet, several clinical trials have already demonstrated their activity in this indication, as illustrated by the results of studies investigating surufatinib, 20 axitinib, 23 pazopanib, 24 and bevacizumab 25 in NET. Nevertheless, no general treatment recommendation can be issued at this stage regarding the use of antiangiogenic drugs in NET of pulmonary origin.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of surufatinib in the US population was assessed in pancreatic NETs and in the European population is currently under research in an open-label phase 2 study (NCT04579679) with different cohorts of patients (Cohort A: NETs of lung origin; Cohort B: NETs of small bowel origin; Cohort C: NETs of non-small bowel, non-pancreas, and non-lung origin; Cohort D: NETs of any origin, DDI substudy) [104] (Table 3). The role of axitinib has been assessed in the AXINET phase II/III study [92] conducted in patients with advanced G1-G2 non-pancreatic NETs, including 71 patients with lung NETs. Patients were randomized (1:1) to receive octreotide LAR with axitinib or placebo.…”
Section: Targeted Therapymentioning
confidence: 99%